COGNITIVE LINGUISTICS AND STEREOTYPES IN IT (TAMADDUN NURI JURNALI, 2024)
Cognitive linguistics studies language as a cognitive mechanism in its transformation and encoding. The goal of linguistics is to understand how the process of perception emerges, categorizes, classifies, and understands the world from one's point of view.